Oxidative Stress Promotes Liver Cancer Metastasis via RNF25‐Mediated E‐Cadherin Protein Degradation - Zhao Huang; Li Zhou; Jiufei Duan; Siyuan Qin; Jingwen Jiang; Haining Chen; Kui Wang; Rui Liu; Minlan Yuan; Xiangdong Tang; Edouard C. Nice; Yuquan Wei; et al. (Advanced Science, 2024)
Abstract Loss of E‐cadherin (ECAD) is required in tumor metastasis. Protein degradation of ECAD in response to oxidative stress is found in metastasis of hepatocellular carcinoma (HCC) and is independent of transcriptional repression as usually known. Mechanistically, protein kinase A (PKA) senses oxidative stress by redox modification in its β catalytic subunit (PRKACB) at Cys200 and Cys344. The activation of PKA kinase activity subsequently induces RNF25 phosphorylation at Ser450 to initiate RNF25‐catalyzed degradation of ECAD. Functionally, RNF25 repression induces ECAD protein expression and inhibits HCC metastasis in vitro and in vivo. Altogether, these results indicate that RNF25 is a critical regulator of ECAD protein turnover, and PKA is a necessary redox sensor to enable this process. This study provides some mechanistic insight into how oxidative stress‐induced ECAD degradation promotes tumor metastasis of HCC.